Flyer Media Lab Natural Science to Improve Student Achievement - Wahyudin Wahid (Jurnal Pendidikan Sains, 2014)
Media Flyer Lab IPA untuk Meningkatkan Prestasi Belajar SiswaAbstract: The aim of this study was to develop Flyer Lab media to improve students achievement in secondary school. The development model used in this study was adapted from 4-D model of Thiagarajan and Semmel. Expert validation results of field study and expert validation results of media, assessment of science teachers, and evaluating the readability and attractiveness of junior high school students obtained in the development stages. The testing stages using a posttest only control group design, involving the experimental group and the control group, each consisting of 47 students. Class experiments using Flyer Lab media obtained higher average value of students achievement than the control class that uses Powerpoint media.Key Words: flyer lab, learning readiness, learning achievementAbstrak: Penelitian ini bertujuan mengembangkan media Flyer Lab IPA untuk meningkatkan prestasi belajar siswa SMP. Model pengembangan yang digunakan dalam penelitian ini diadaptasi dari model 4-D Thiagarajan dan Semmel. Studi kepustakaan dan survei lapangan dilakukan pada tahap pendahuluan. Validasi ahli bidang studi dan media, penilaian dari guru IPA, serta penilaian keterbacaan dan ketertarikan bahan ajar dari siswa SMP diperoleh pada tahap pengembangan. Tahap pengujian menggunakan desain posttest only control group, melibatkan kelompok eksperimen dan kelompok kontrol yang masing-masing terdiri dari 47 siswa. Kelas eksperimen yang menggunakan media Flyer Lab memiliki nilai rata-rata prestasi belajar lebih tinggi daripada kelas kontrol yang menggunakan media Powerpoint. Kata kunci: flyer lab, kesiapan belajar, prestasi belajar